THE INFLUENCE OF FUNCTIONAL ABILITY ON THE QUALITY OF LIFE OF ELDERLY WITH THE SIX MINUTE WALK TEST AND THE ONE MINUTE SIT AND STAND TEST. (CIPEEX, 2022)
AGING IS A PROGRESSIVE AND IRREVERSIBLE FACTOR THAT DEALS WITH A GRADUAL PROCESS OF MOTOR AND SENSORY LOSSES OVER TIME. ONE OF THE FUNDAMENTAL PROCESSES OF AGING IS THE REDUCTION OR LOSS OF FUNCTIONAL STRENGTH, WHICH DIRECTLY AFFECTS THE ABILITY AND PRACTICE OF DAILY LIFE ACTIVITIES.&NBSP;
Keywords: Seniors; Functional capacity; Six-minute walk test; One minute sit and stand test.